EFEKTIVITAS PENGGUNAAN TAKTIK PENGARUH DALAM KEPEMIMPINAN KEPALA DAERAH TERHADAP KOMITMEN TUGAS DAN KOMITMEN ORGANISASI BAWAHAN PADA PEMERINTAH KABUPTEN/KOTA DI PROVINSI GORONTALO - Ikram Muhammad (Program Studi Ilmu Pemerintahan, 2023)
Task commitment and organizational commitment are the main driver of individual and organizational performance in the public sector. This paper considers that regional heads who consistently use influence tactics in rational persuasive behavior will be positively correlated to task commitment and organizational commitment. The result of a survey on 165 heads of Regional Government Agency showed that only two tactics in rational influencing behavior namely rational persuasion tactic and inspiring tactic which are positively and significantly correlated to task commitment and organizational commitment of subordinates in local government of Gorontalo province.